Desenvolvimento de nanopartículas de quitosana contendo carvacrol frente a Leishmania infantum: estudo preliminar - Borges, Joyce Cordeiro (2022)
The Leishmaniases are neglected tropical infectious diseases caused by protozoa of the genus Leishmania and transmitted by sand flies (Lutzomyia). Visceral leishmaniasis (VL) is the most severe form of the disease. The treatment lines for VL include intravenously administered drugs that cause adverse effects in patients. Carvacrol (CAR), is a phenolic monoterpene that has shown strong activity against Leishmania spp. Chitosan (Chi) is a biopolymer with excellent chemical and biological properties, and acts as a component of several drug delivery systems in various therapies and in particular in anti-leishmania activity. Several studies have proposed the use of nanocarriers as delivery systems using polymeric chitosan nanoparticles, as a strategy to improve efficacy and safety in the treatment of leishmaniasis. The hypothesis of this study of CAR encapsulation in polymeric chitosan nanoparticles (NPChi) aims to answer whether its therapeutic effects can potentiate the treatment for leishmaniasis. Thus, the present work aimed to develop, characterize NPChi containing CAR (NPCar) and evaluate the anti-leishmania activity against L. infantum. The NPChi were prepared by the ionic gelation method varying the concentrations of Chi:TPP respectively between 0.05%, 0.1% and 0.2% and 0.05%, 0.1% and 0.5%, obtaining 9 samples. The in vitro activity assays were performed against promastigotes of L. infantum by the MTT test and the results were analyzed with the aid of GraphPad Prisma 5.0 software. Among the prepared formulations, sample A2 (0.1%Chi:0.05%TPP g/v), had the best results, with particle sizes at 89.43 ± 0.774 nm, polydispersity 0.168 and Zeta potential 12.8 mV. After encapsulation of the CAR (1mg/mL) in formulation A2, it showed a particle size of 245.9 nm, polydispersity 0.175 and the high zeta potential 15.4 mV. Preliminary analysis of in vitro antileishmania activity demonstrated strong inhibition of L. infantum promastigotes by NPCar with an IC50 of 2.659 μg/mL. The results of the present study demonstrate that the obtained NPCar maintain characteristics suitable for drug delivery systems with high homogeneity and stability, and preliminary studies in L. infantum demonstrated that NPCar may be promising candidates for visceral leishmaniasis.